2020
DOI: 10.1152/ajpheart.00456.2019
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin contributes to thrombus formation and vascular injury by interfering with platelet function

Abstract: Doxorubicin therapy in mice (antitumor dosage) markedly enhanced platelet functions measured as agonist-induced platelet aggregation, degranulation, and adhesion to endothelial cells, actions leading to thrombus formation and thrombosis-independent vascular injury. Clopidogrel treatment ameliorated thrombus formation and vascular toxicity induced by doxorubicin via inhibiting platelet activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…These altered biochemical alterations were supported by histological lesions characterized by myocyte congestion and coronary intravascular microthrombi formation. DOX has been previously reported to profoundly reduce vascular blood flow, disintegrate vascular endothelium, and promote GPIIb/IIIa-mediated platelet adhesion and aggregation, all resulting in microthrombi formation [ 56 58 ]. The fact that IGESE prevented microthrombi formation in DOX-treated coronary vasculature as evidenced by histopathological results of this study highlighted the possible inherent antithrombotic potential of IGESE ; although, further studies are still needed in this respect in order to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…These altered biochemical alterations were supported by histological lesions characterized by myocyte congestion and coronary intravascular microthrombi formation. DOX has been previously reported to profoundly reduce vascular blood flow, disintegrate vascular endothelium, and promote GPIIb/IIIa-mediated platelet adhesion and aggregation, all resulting in microthrombi formation [ 56 58 ]. The fact that IGESE prevented microthrombi formation in DOX-treated coronary vasculature as evidenced by histopathological results of this study highlighted the possible inherent antithrombotic potential of IGESE ; although, further studies are still needed in this respect in order to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed doxorubicin had vascular toxicity and increase the chance of thrombus formation [125]. In this case, treating the restenosis patients with doxorubicin could have high risk of side effects.…”
Section: Theranostic Nanoparticles For Vascular Injury and Restenosismentioning
confidence: 96%
“…The promise of such an approach is evident in studies involving chemotherapy drug (e.g., doxorubicin) encapsulation in actual platelets for tumor‐targeted delivery in lymphoma 102,103 . However, studies have also shown that doxorubicin can directly impact platelet activation and functions leading to thrombotic and thrombocytopenic side effects 104,105 . This provides a strong rationale to use platelet‐mimetic nanoparticles as potential carrier platforms for doxorubicin and other drugs to avoid effects on endogenous platelets while enabling targeted delivery to cancer cells.…”
Section: Platelet‐inspired Nanomedicine Approaches For Treating Cancermentioning
confidence: 99%